Struktura relacji w pamiętnikach Bogusława Kazimierza Maskiewicza - Bauer, Marcin (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The paper describes the structure of relation in two diaries of Bogusław Kazimierz Maskiewicz. Its author was a 17th century noble who served as a hussar and managed an estate in Lithuania. Maskiewicz has left two memoirs. First of them mainly relates the period of 1648-1649 - initial years of war with Cossack uprising in Ukraine led by Bohdan Chmielnicki, in which Maskiewicz has fought in the cavalry regiments of dukes Jeremi Wiśniowiecki and Bogusław Radziwiłł. The second shows war from another perspective: it reflects the time of Russian invasion of Lithuania in 1660 seen by the landlord, inhabitant of occupied country. The essay also briefs the biography of В. K. Maskiewicz and the current state of research on analyzed text.